Human immunodeficiency virus type 2 (HIV-2) dynamics and whole genome deep sequence analysis in Mauritian-origin cynomolgus macaques (Macaca fascicularis). Issue Volume 1(2019)Issue A (8th March 2019) - Ham, Claire; Ferguson, Debbie; Jenkins, Adrian; Hall, Jo; Almond, Neil; Berry, Neil
Abstract : Human immunodeficiency virus type 2 (HIV-2) is a pathogenic human retrovirus with a distinct natural history and lineage derivation from pandemic HIV-1. HIV-2 infections in humans are the result of zoonotic transmission from sooty mangabey monkeys naturally infected with SIVsm. Unlike HIV-1, HIV-2 infects other non-human primate species, including baboons and macaques. We determined the infectivity and infection kinetics of a Gambian-origin HIV-2 isolate HIV-2SBL6669 strain in Mauritian-derived cynomolgus macaques (MCM) in the context of a heterologous superinfection resistance study. The ability of HIV-2 to replicate in unvaccinated MCM with limited host genetic MHC and TRIM5 spectrum was determined where the kinetics of plasma HIV-2 RNA mimic the phenotypic response typically observed in HIV-2-infected humans. HIV-2SBL669 replication is not completely restricted in this species and may establish a persistent infection. This is determined by moderate peak viral loads (105–6 log10 HIV-2 RNA copies/ml) controlling to a low level determined by qRT-PCR and detectable in-situ hybridisation signals in lymphoid tissue 20 weeks after challenge. In MCM vaccinated for 20 weeks with an attenuated SIV, we observed high levels of superinfection resistance as determined by virus-specific PCR analysis of tissues and low total plasma viral RNA levels in vaccinates compared to unvaccinated HIV-2 controls. Recovery of whole viral genome and next generation sequence analysis of challenge controls, including low-level breakthrough variants characterises viral challenge and vaccine-escape viruses. HIV-2 in cynomolgus macaques recapitulates many of the features of HIV-2 infections in humans.